EFFECT OF DIETARY ASTAXANTHIN ON PIGMENT ACCUMULATION IN THE MUSCLE-SKIN, RESISTANCE TO SALINITY STRESS AND COPPER TOXICITY OF COMMERCIAL CLOWNFISH, Amphiprion ocellaris - Lam, Ho Son; Ngoc, Phan Thi (Vietnam Journal of Marine Science and Technology, 2018)
This study examined the influence of Astaxanthin added in feed on pigment accumulation in the muscle-skin, as well as resistance to salinity stress and copper toxicity of clownfish (Amphiprion ocellaris). Mean length of fish was 33.05 ± 3.29 mm. Five experiments were performed with synthetic Astaxanthin contents: 0, 50, 100, 150 and 200 mg/kg diets. After 8 weeks of the experiment, the pigment accumulation of Astaxanthin in the muscle-skin of clownfish was the lowest in the control treatment of 2.11 ± 0.13 µg/g, while these treatments of 150 and 200 mg/kg diets were over 10 µg/g. The treatments of 150 and 200 mg Astaxanthin/kg increased the resistance to copper toxicity and salinity stress test of the fish. The resistance of the fish was longer (>50 minutes) compared to the control (42.4 minutes) in an environment with salinity of 0‰ (p